Improving quality of life in patients with hidradenitis suppurativa: a therapeutic view. (December 2012) - Dufour, Deirdre Nathalie; Esmann, Solveig; Jemec, Gregor BE
Hidradenitis suppurativa is a chronic recurrent inflammatory skin disease with abscess formation and scarring predominantly in the inverse areas. The disease is often difficult to treat and patients experience a decreased quality of life (QoL) and related psychosocial morbidity. Current knowledge on improving QoL in patients with hidradenitis suppurativa is therefore reviewed. The literature is limited but indicates that there are two ways of improving patients' QoL: therapy of the somatic disease or psychosocial interventions.